Exploring customer online reviews for new product development: The case of identifying reinforcers in the cosmetic industry. (23rd August 2019) - Haddara, Moutaz; Hsieh, Jenny; Fagerstrøm, Asle; Eriksson, Niklas; Sigurðsson, Valdimar
Abstract : This study analyzes online customer reviews in order to investigate customers' preferences regarding cosmetic products. Based on the marketing firm theory, this research explores the possibility of enhancing the bilateral contingent relationships between the customer and the marketing firm within the cosmetics domain. Hence, this study applies market‐search concepts by extracting customer reviews and employing text analytics to identify reinforcers and factors in cosmetic products, which customers are expecting, and their sentiments towards them. Our results suggest that some reinforcers are shared among all customers, but some vary among the different customer segments based on their age and skin tone.